Uji Serologi Terhadap Antigen Flagella Dari Isolat Salmonella typhi Di Makassar Dengan Teknik Enzyme Linked Immunosorbent Assay (ELISA - Musjaya M. Guli (Biocelebes, 2007)
Typhoid fever is a disease most prevalent in countries in detecting typhoid fever.  The aim of the was to discover the effectifeness of local antigens flagella to detect antibody of the typhoid fever patiens. The method applied was serological test of Elisa techniques to detect the serum titer obtained from Wahidin Sudirohusodo  General  Hospital.  The  study  was  conducted  at  the   immunology  and  Microbiology Molecular  Labrotory  of    Medicine  Faculty,  Hasanuddin  University  in  Makassar.  The  data  were analyzed by using  Wilcixon sign  test. The result of the study indicate that local antigen flagella can be used as a standard antigen in diagnosing typhoid fever.Key words: Elisa, flagella antigen (H), Salmonella typhy